Analisis Implikatur pada Podcast Crazy Nikmir Real - Krisnawati, Ni Luh Putu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This research will analyze implicatures in a conversation that can have implicit or explicit meanings. The data source used is the Youtube channel of a famous and controversial Indonesian artist Nikita Mirzani, named Crazy Nikmir Real. The episode used is the episode when interviewing Deddy Corbuzier which is divided into two episodes with the title Adu Debat Berbobot!!! Cuma Nyai Yang Berani Adu Debat Begini Sama Dedy Corbuzier!!! dan Kalah Telak!!! Begini Pengakuan Dedy Corbuzier Yang Bikin Nikita Speechless!!! . Furthermore, the data will be analyzed using theories related to the types of implicatures and politeness maxims proposed by Grace (1975) and will be explained using qualitative descriptive methods. The findings show that both types of implicatures are found in the Crazy Nikmir Real podcast, namely conversational implicatures with three data and conventional implicatures with two data. Flouting from the politeness maxim that occur are the maxim of relevance, maxim of quality and maxim of manner.